Synthesis of naphthoquinone derivatives with some study on percentage rate of formation for pyridinium salt / Nor Shazana Mohamed Daud - Mohamed Daud, Nor Shazana (2010)
The focus of this study is to synthesize the naphthoquinone derivative via the reaction of pyridinium salt with methyl naphthoquinone. The starting material 2,4-dibromoacetophenone reacted with pyridine to produce pyridinium salt in 96.29% yield. The further reaction was done, producing naphthoquinone derivative in 25.71% yield in the mixture of isomer red and yellow compounds. The product consists isomer of two compounds was separated using column chromatography. The isolated red and yellow compounds was characterized using IR and NMR analysis. The study on the times of refluxing was also performed in order to determine the optimum time of salt formation. The formation of pyridinium salt is directly proportional with time of refluxing.